2012
DOI: 10.1111/j.1600-0447.2012.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein, early life stress, and wellbeing in healthy adults

Abstract: Objective To determine whether C-reactive protein (CRP) can serve as a marker for alterations in immune function prior to the manifestation of significant psychiatric and medical disorders. Method Ninety-two healthy adults were recruited from the community and determined to be free of psychiatric or medical disorders. The concentration of plasma CRP from a single resting sample was examined in relation to current mental and physical health as well as to self-reported history of early life adversity. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 86 publications
2
18
0
2
Order By: Relevance
“…In contrast to our study, Slopen’s (2010) study included subjects who had a history of diabetes and cardiovascular disease and medications which may alter basal cytokine levels. In support of the present findings, no association was found between plasma CRP levels and childhood adversity in healthy adults (Carpenter, Gawuga, Tyrka, & Price, 2012). …”
Section: Discussionsupporting
confidence: 87%
“…In contrast to our study, Slopen’s (2010) study included subjects who had a history of diabetes and cardiovascular disease and medications which may alter basal cytokine levels. In support of the present findings, no association was found between plasma CRP levels and childhood adversity in healthy adults (Carpenter, Gawuga, Tyrka, & Price, 2012). …”
Section: Discussionsupporting
confidence: 87%
“…Our lifestyles are increasingly sedentary, with a lack of PA, particularly for those living in urban centres currently recognised as a major health problem worldwide . Epidemiological studies consistently suggest that adequate PA is associated with fewer depressive symptoms, while physical inactivity may be a risk factor for the development of depressive symptoms . This may be true at both ends of the lifespan.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, microglial cells and immune mediators such as cytokines are well‐recognized modulators in the development of central sensitization, hyperalgesia, and allodynia (Watkins et al, ; Latremoliere and Woolf, ). Investigating the relationship among early‐life adversity, alterations in immune mediators, and pain has revealed that, in a study of 92 individuals, levels of C‐reactive protein were directly associated with somatic pain complaints; however, this relationship was not impacted by self‐reported early‐life adversity (Carpenter et al, ). Further studies are required to determine whether other inflammatory markers may mediate the impact of early‐life adversity on pain, in healthy individuals and in those with chronic pain conditions.…”
Section: Neurobiological Mechanisms Underlying the Association Betweementioning
confidence: 99%